Disparities in the unmet mental health needs between LGBTQ+ and non-LGBTQ+ populations during COVID-19 in the United States from 21 July 2021 to 9 May 2022 - Chen, Shanquan; Wang, Yuqi; She, Rui; Qin, Pei; Ming, Wai-Kit (Frontiers in Medicine, 2022)
Background Evidence highlighted the likelihood of unmet mental health needs (UMHN) among LGBTQ+ than non-LGBTQ+ populations during COVID-19. However, there lacks evidence to accurately answer to what extent the gap was in UMHN between LGBTQ+ and non-LGBTQ+ populations. We aim to evaluate the difference in UMHN between LGBTQ+ and non-LGBTQ+ during COVID-19. Methods Cross-sectional data from Household Pulse Survey between July 21, 2021 and May 9, 2022 were analyzed. LGBTQ+ was defined based on self-reported sex at birth, gender, and sexual orientation identity. UMHN was assessed by a self-reported question. Multivariable logistic regressions generated adjusted odds ratios (AODs) of UMHN, both on overall and subgroups, controlling for a variety of socio-demographic and economic-affordability confounders. Findings 81267 LGBTQ+ and 722638 non-LGBTQ+ were studied. The difference in UMHN between LGBTQ+ and non-LGBTQ+ (as reference) varied from 4.9% (95%CI 1.2%-8.7%) in Hawaii to 16.0% (95%CI 12.2%-19.7%) in Utah. In multivariable models, compared with non-LGBTQ+ populations, LGBTQ+ had a higher likelihood to report UMHN (AOR=2.27,95%CI 2.18-2.39), with the highest likelihood identified in transgender (AOR=3.63,95%CI 2.97-4.39); Compared with LGBTQ+ aged 65+, LGBTQ+ aged 18-25 had a higher likelihood to report UMHN (AOR=1.34,95%CI 1.03-1.75); Compared with White LGBTQ+ populations, Black and Hispanic LGBTQ+ had a lower likelihood to report UMHN (AOR=0.72,95%CI 0.63-0.82; AOR=0.85, 95%CI 0.75-0.97, respectively). Interpretation During the COVID-19, LGBTQ+ had a substantial additional risk of UMHN than non-LGBTQ+. Disparities among age groups, subtypes of LGBTQ+, and geographic variance were also identified.